2015
DOI: 10.1001/jamainternmed.2015.3558
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions About Smoking Cessation in the Context of Lung Cancer Screening

Abstract: Broad adoption of lung cancer screening may inadvertently lead to negative population health outcomes if it is perceived as a substitute for smoking cessation.OBJECTIVE To understand views on smoking cessation from current smokers in the context of being offered lung cancer screening as a routine service in primary care. DESIGN, SETTING, AND PARTICIPANTSAs an ancillary study to the launch of a lung cancer screening program at 7 sites in the Veterans Health Administration, 45 in-depth semi-structured qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
87
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 36 publications
3
87
2
1
Order By: Relevance
“…On one hand, however, there is some evidence that positive LDCT screening results (e.g., detection of nodules) are associated with increases in quit rates and in reducing relapse among recent quitters (23, 24, 27, 29). On the other hand, screening may have paradoxical effects because others with a screen-detected nodule may be too scared or anxious to tackle quitting smoking (30), and patients with a normal LDCT screening result may feel little urgency to quit (31). Of note, among all persons screened, 80 to 86% have a normal or low-risk result (American College of Radiology Lung CT Screening Reporting and Data System [“Lung-RADS”] category 1 or 2) (32, 33).…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, however, there is some evidence that positive LDCT screening results (e.g., detection of nodules) are associated with increases in quit rates and in reducing relapse among recent quitters (23, 24, 27, 29). On the other hand, screening may have paradoxical effects because others with a screen-detected nodule may be too scared or anxious to tackle quitting smoking (30), and patients with a normal LDCT screening result may feel little urgency to quit (31). Of note, among all persons screened, 80 to 86% have a normal or low-risk result (American College of Radiology Lung CT Screening Reporting and Data System [“Lung-RADS”] category 1 or 2) (32, 33).…”
Section: Resultsmentioning
confidence: 99%
“…25 Another key aspect that needs to be balanced is the potential for unanticipated indirect effects. For example, a study by Zeliadt et al 26 revealed that smokers would be less likely to quit the habit if an effective lung cancer screening program was offered.…”
Section: 20mentioning
confidence: 99%
“…This analysis involved 2 critical assumptions about the psychological effects of screening on heavy smokers: that the cascade of screening leads to few psychological harms and that screening has no effect on smoking behavior. The qualitative study by Zeliadt et al 5 in this issue of JAMA Internal Medicine should prompt us to revisit these 2 assumptions. Although many acknowledge the potential psychological effects of lung cancer screening, 6 we have little useful evidence to help determine the frequency and burden of the potential psychological harms of lung cancer screening.…”
mentioning
confidence: 99%
“…Studies that do not use sensitive condition-specific measurement instruments are unlikely to detect the types of psychological effects that may result from screening. This issue is where the qualitative analysis by Zeliadt et al 5 is helpful. The investigators use a more sensitive qualitative approach to gain a richer understanding of the association between screening and heavy smokers' sense of their health.…”
mentioning
confidence: 99%
See 1 more Smart Citation